2020
DOI: 10.1177/0021998320929417
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis and mechanical characterization of Al 6061/alumina/bagasse ash hybrid reinforced metal matrix composite using vacuum-assisted stir casting method

Abstract: This experimental analysis aimed to fabricate low cost, lightweight metal matrix composite using Al 6061 as matrix material and alumina (Al2O3) and bagasse ash as reinforcing material through stir casting process. In this process one cast of single reinforced composite (Al 6061/5 wt% Al2O3) and three casts of hybrid reinforced composite (Al 6061/5 wt% Al2O3/ 4, 6, 8 wt% bagasse ash) were developed and processed as per ASTM standards followed by mechanical (micro-hardness, ductility, compression, tensile, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Brittle nature of reinforcement (LBA and B 4 C) particles performs an essential role in decreasing the impact strength of the composites. Comparable results have also been informed by Chandla et al 28 where bagasse ash and Al 2 O 3 reinforcements were used for fabrication of composites. Bello et al 42 in their study reported the decrease in impact strength of composites reinforced with coconut shell microparticles.…”
Section: Mechanical Characterizationmentioning
confidence: 66%
See 2 more Smart Citations
“…Brittle nature of reinforcement (LBA and B 4 C) particles performs an essential role in decreasing the impact strength of the composites. Comparable results have also been informed by Chandla et al 28 where bagasse ash and Al 2 O 3 reinforcements were used for fabrication of composites. Bello et al 42 in their study reported the decrease in impact strength of composites reinforced with coconut shell microparticles.…”
Section: Mechanical Characterizationmentioning
confidence: 66%
“…Particle agglomerates, the presence of voids, clusters, and rise in porosity decreases the hardness of the composites. 23,28 Compressive strength. Compressive behaviour of the single and hybrid-reinforced composites along with the base alloy are shown in Figure 10.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Their presence makes SCB an ultimate material as a reinforcement fiber in the development of new material with exceptional physical and chemical properties [70,71]. Chandla et al, [72] reinforced varying content of bagasse ash in Al6061/5wt% Al 2 O 3 based composites via stir casting technique and observed an increase in hardness as well as the tensile strength of the composites with increasing bagasse ash content.…”
Section: Sugarcane Bagasse Ash (Scba)mentioning
confidence: 99%
“…The development MMCs were characterized to indicate improvement of properties over un-reinforced alloy. Chandla et al. (2020) Groundnut shell ash (GSA) 17.6 5.93 3.43 9.89 9.79 18.3 0.22 4.85 0.08 Stir casting Al 6063 alloy was reinforced GSA at 3, 6, 9, 12 wt.% of the ash.…”
Section: Biomass Materials Utilization As Reinforcements In Metal Matrix Compositementioning
confidence: 99%